Clinicians’ assumptions about Sami culture and experience providing mental health services to Indigenous patients in Norway - Dagsvold, Inger; Møllersen, Snefrid; Blix, Bodil Hansen (Transcultural Psychiatry, 2020)
This qualitative study explores Sami and non-Sami clinicians’ assumptions about Sami culture and their experiences in providing mental health services to Sami patients. The aim is to better understand and improve the ways in which culture is incorporated into mental health services in practice. Semi-structured interviews were conducted with 20 clinicians in mental health outpatient clinics in the northern Sami area in Troms and Finnmark County in Norway. The findings show that clinicians’ conceptualizations of culture influence how they take cultural considerations about their Sami patients into account. To better integrate culture into clinical practice, the cultures of both patient and clinician, as well as of mental health care itself, need to be assessed. Finally, the findings indicate a lack of professional team discussions about the role of Sami culture in clinical practice.